Biochemical traits of asparagus cultivars and quality changes in two differently coloured genotypes during cold storage. (March 2019) - Sergio, L.; Gonnella, M.; Renna, M.; Linsalata, V.; Gatto, M.A.; Boari, F.; Di Venere, D.
Abstract: The aim was to evaluate morpho-biochemical traits in four asparagus cultivars ('Early California', 'Grande', 'Purple Passion', and 'Vegalim'), and qualitative changes in 'Grande' and 'Purple Passion' during storage in air or passive modified atmosphere packaging (MAP, 15% O2 – 5% CO2 ), at 4 °C for 28 days. 'Early California' showed the highest total phenolic (TPh) and quercetin-3-rutinoside (rutin) content, and the highest total antioxidant activity (TAA). 'Purple Passion' was the richest in glucose and total sugars, while 'Early California' the least rich in sucrose. The nitrate content was lower than 100 mg kg −1 FM and potassium on average 280 mg 100 g −1 FM. The MAP reduced weight loss, ensuring product turgidity and mitigating the cold storage stress. In the first 7 days in storage, 'Purple Passion' showed higher values of TPh, rutin and TAA. Afterwards, TPh content increased in both cultivars in MAP. During storage, sugars gradually decreased, except sucrose in 'Purple Passion', increased by almost 40% after 14 days. 'Grande' and 'Purple Passion' spears showed optimal overall quality up to 14 days-storage, but they could not be stored for more than 21 days. Moreover, MAP allowed to preserve or enhance antioxidant properties of asparagus during the whole storage. Highlights: 'Early California' was the richest in total phenols, rutin and antioxidant activity. Nitrate content was very low in each cultivar, less than 100 mg kg −1 FM. After 7 days storage 'Purple Passion' had higher total phenols, rutin and antioxidant activity. MAP (5% CO2 /15% O2 ) can preserve asparagus phenolics and antioxidant properties.